Answer:
d(4) = 64
Explanation:
d(1) = 13
d(n) = d(n - 1) + 17
where
n is the nth term
To find the 4th term we must first find the second term use it to find the 3rd term and use the 3rd term to find the 4th term
So we have
For the 2nd term
That's d(2)
We have
d(2) = d(2-1) + 17
d(2) = d(1) + 17
But d(1) = 13
d(2) = 13 + 17 = 30
For the 3rd term d(3)
That's
d(3) = d(3 - 1) + 17
d(3) = d(2) + 17
d(3) = 30 + 17 = 47
For the 4th term that's d(4)
We have
d(4) = d(4 - 1) + 17
d(4) = d(3) + 17
d(4) = 47 + 17
We have the final answer as
d(4) = 64
Hope this helps you